Use of an audience response system to maximise response rates and expedite a modified Delphi process for consensus on occupational health. Issue 1 (December 2016) - Aw, Tar-Ching; Loney, Tom; Elias, Anza; Ali, Soha; Ádám, Balázs
Abstract Background Different methods have attempted to obtain consensus on occupational health issues. The objective of this paper is to describe a modified three-stage Delphi process that uses a wireless audience response system to enable consensus to be attained in a single day and to maximise response rates. The modified Delphi approach required: a) agreeing the topic/s of interest for which consensus is sought, b) identifying key stakeholders whose opinions are required; c) assembling the stakeholders for a one-day event. Participants' opinions were recorded primarily through use of a system of individual wireless audience response devices ('clickers') linked to a computer. Providing immediate feedback enabled the audience to consider the group's views before proceeding to the next stage. From an initial round of responses, participants were asked to narrow their choices to any five preferred options. A third round was conducted, using the 'clickers' to rank 5 of the most popular group options. Through this iterative exercise, stakeholder consensus was achieved after three decision rounds. Results The use of the modifications and the wireless audience response system described enabled stakeholders to provide a group view on specific occupational health issues e.g. priorities or barriers or resources needed. Completing the three-stage iterative exercise in a day maximised the response rate with advantages for both the participants and the researchers. Careful design of the protocol is essential, with a team familiar with information technology to ensure smooth execution of the various stages. Conclusions Modification of the Delphi method with the use of a wireless audience participation system facilitates rapid consensus.